(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Individual livestock farmers in Cikedung Subdistrict, Indramayu Regency, play a crucial role in supporting national beef production. However, they encounter significant challenges, including limited technological access, weak management efficiency, restricted market access, and minimal institutional support. This study aims to evaluate the sustainability of individual rearing systems using the Multidimensional Scaling (MDS) analysis method through the Rap-UPTS model, covering five dimensions: economic, socio-cultural, ecological, legal-institutional, and technological-infrastructure. A total of 15 respondents were involved, and the analysis employed leverage and Monte Carlo techniques. Findings revealed a “less sustainable” status, with the highest score in the ecological dimension (49.80) and the lowest in the legal-institutional dimension (37.61). The model was deemed valid, with a stress value of 0.133 and an R² of 0.95. Strengthening institutional support and enhancing human resource capacity are key strategies for improving sustainability in smallholder livestock systems.